Peramalan Pertumbuhan Dana Pihak Ketiga (DPK) Bank Rakyat Indonesia (BRI) Menggunakan Model ARIMA Berbasis Data Publik BPS - Vifin Nadzary A; Khoirony, Nur Cahya; Nurhalizah, Siti; Helmi; Susetyo, Achmad Budi (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
Third Party Funds (TPF) play a crucial role as the main source of financing for the banking sector, as they determine a bank’s liquidity position and its ability to perform intermediation functions. Bank Rakyat Indonesia (BRI), as one of the leading banks in Indonesia with a strong focus on micro, small, and medium enterprises (MSMEs), faces fluctuating growth in Third Party Funds due to changing economic conditions. This study aims to analyze the historical pattern and forecast the growth of BRI’s Third Party Funds using the Autoregressive Integrated Moving Average (ARIMA) model based on public data published by the Central Bureau of Statistics (BPS). This research adopts a quantitative approach with time series analysis. The analytical stages include descriptive analysis, stationarity testing using the Augmented Dickey-Fuller (ADF) test, ARIMA model identification and estimation, diagnostic testing, and forecasting. The results indicate that the growth of BRI’s Third Party Funds can be effectively modeled using the ARIMA approach after achieving stationarity. The selected ARIMA model successfully captures historical fluctuations and provides relatively stable short-term forecasts of Third Party Fund growth. These findings suggest that the ARIMA model based on publicly available BPS data is a reliable forecasting tool for supporting strategic planning and liquidity management in the banking sector. This study is expected to contribute empirically to the literature on financial time series forecasting and banking performance analysis.